Information seeking behavior of older adults in a public library in Japan - Uda, Norihiko (2021)
Background. Services for older adults are becoming accepted as a separate user service category at Japanese public libraries. From the perspective that older adults are themselves supposed to support the community in this super-aged society, there is a growing need to give positive assistance to older adults as library patrons and information seekers. Objective. This paper examines the information seeking behavior of older adults at a public library, including how they select information search tools, as well as their reasons and perception underlying such behavior. Methods. Experiments were conducted at a public library to investigate actual information behavior, and interviews were carried out to clarify user perceptions of public libraries and user needs. Results. The information seeking behavior of older adults at public libraries can be categorized into three patterns: Case 1 where the Library Usage Frequency is High; Case 2 where the Library Usage Frequency is Low and There is Preference for Search Method; and Case 3 where the Library Usage Frequency is Low and There is No Preference for Search Method. Contributions. The study has identified some information seeking behavior patterns of older adults at public libraries. Some challenges in current services are identified, and directions for future services to older adults are proposed.